Tensile behavioral characteristics of lightweight carbon textile-reinforced cementitious composites. (1st October 2022) - Pham, Huu Hiep; Dinh, Ngoc Hieu; Kim, Seung-Hee; Park, Sang-Hyun; Choi, Kyoung-Kyu
Abstract: The present study experimentally investigated the tensile behavioral characteristics of newly developed lightweight textile-reinforced cementitious composites (TRC). Two common forms of carbon textile fabrics typically used for structural applications were employed: uncoated (dry) and coated. Expanded glass aggregates made from industrial refractory materials with fine particle sizes of 0.25–0.5 mm and a mineral admixture (silica fume) were used to develop the lightweight cement-based matrix. The main test parameters in this study included the expanded glass-to-binder ratio (EG/B ratio), surface coating methods used for the textile fabrics, and volume dosages of the short polyvinyl alcohol (PVA) fibers used to modify the cement-based matrix. Tensile tests were performed based on RILEM TC 232-TDT standard. The experimental results indicate that the failure modes and tensile crack characteristics of the lightweight TRC composites are significantly affected by the surface coating methods used for the textile fabrics and the volume fraction(s) of the short PVA fibers used to modify the cement-based matrix. In addition, the use of different EG/B ratios in the matrix and coating methods for the textile fabrics influence the overall tensile performance of the lightweight TRC composites. The addition of short PVA fibers in the lightweight cement-based matrix significantly enhances the tensile performance of TRC coupons in both the pre-cracking and post-cracking stages. Highlights: The tensile performance of the newly developed lightweight TRC was investigated. EG aggregates made from industrial waste were employed to fabricate the cement-based matrix. Different coating methods were employed and investigated for carbon textile fabrics. Dispersed short PVA fibers were used to modify the cement-based matrix. The research shows the potential application of lightweight TRC for the precast industry.